Predicting Patterns of Intimate Partner Violence Perpetration From Late Adolescence to Young Adulthood - Saint-Eloi Cadely, Hans (Journal of interpersonal violence, 2021)
Saint-Eloi Cadely et al. found longitudinal patterns for the perpetration of both psychological and physical intimate partner violence (IPV), including actively and minimally aggressive patterns. The current study builds on these findings by examining four theory-derived variables (interparental aggression, social-information processing [SIP] biases, relationship insecurities [preoccupied and fearful], and discontinuity in relationship partner over time) as predictors of membership within these patterns, using multinomial logistic regression. The analysis sample consisted of 484 participants who were romantically involved at least once during the eight waves of data collection from the ages of 18 to 25. In predicting psychological IPV, more SIP biases, higher levels of a preoccupied insecurity, and less discontinuity in relationship partners over time differentiated the actively aggressive patterns from the minimally aggressive pattern. In addition, two actively aggressive patterns of psychological IPV differed in terms of SIP biases and discontinuity in romantic partners. Specifically, more SIP biases and less discontinuity in romantic partnerships distinguished the extensively aggressive pattern from the pattern that mainly consisted of minor types of aggression. In predicting physical IPV, the aggressive pattern differed from the nonaggressive pattern in terms of more interparental aggression, more SIP biases, and more relationship insecurities. The findings that developmental patterns of IPV can be predicted by social and psychological factors may aid both developmental theory and practice.